2000
DOI: 10.1029/1999jd900779
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and fate of selected oxygenated organic species in the troposphere and lower stratosphere over the Atlantic

Abstract: Abstract. A large number of oxygenated organic chemicals (peroxyacyl nitrates, alkyl nitrates, acetone, formaldehyde, methanol, methylhydroperoxide, acetic acid and formic acid) were measured during the 1997 Subsonic Assessment (SASS) Ozone and Nitrogen Oxide Experiment (SONEX) airborne field campaign over the Atlantic. In this paper, we present a first picture of the distribution of these oxygenated organic chemicals (Ox-organic) in the troposphere and the lower stratosphere, and assess their source and sink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
348
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(378 citation statements)
references
References 39 publications
23
348
3
1
Order By: Relevance
“…The direct anthropogenic contribution (e.g., solvent emission) is just a few percent. These numbers are all based on the recent budget of Jacob et al (2005) and the values have considerable uncertainty, and they differ substantially from previous budgets (Singh et al, 2000;Heikes et al, 2002;Galbally and Kirstine, 2002;von Kuhlmann et al, 2003a, b). Methanol is involved in HO x chemistry because the reaction with OH forms the CH 3 O and H 2 COH radicals, which rapidly react with O 2 to give HO 2 and H 2 CO. Formaldehyde chemistry produces additional HO 2 radicals and CO so methanol is a significant source of both H 2 CO and CO (Palmer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The direct anthropogenic contribution (e.g., solvent emission) is just a few percent. These numbers are all based on the recent budget of Jacob et al (2005) and the values have considerable uncertainty, and they differ substantially from previous budgets (Singh et al, 2000;Heikes et al, 2002;Galbally and Kirstine, 2002;von Kuhlmann et al, 2003a, b). Methanol is involved in HO x chemistry because the reaction with OH forms the CH 3 O and H 2 COH radicals, which rapidly react with O 2 to give HO 2 and H 2 CO. Formaldehyde chemistry produces additional HO 2 radicals and CO so methanol is a significant source of both H 2 CO and CO (Palmer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Field and laboratory measurements have been carried out to characterize methanol sources and sinks. By integrating this knowledge into global chemistry and transport models, global annual budgets have been constructed (Singh et al, 2000;Heikes et al, 2002;Galbally and Kirstine, 2002;Tie et al, 2003;von Kuhlmann et al, 2003;Jacob et al, 2005;Millet et al, 2008;Stavrakou et al, 2011). Terrestrial plants have been found to be a major source of atmospheric methanol, with an annual global emission ranging from 75 to 280 Tg y À1 and constituting 60e80% of the total source strength.…”
Section: Introductionmentioning
confidence: 99%
“…Among all atmospheric hydrocarbons, methanol (CH 3 OH) is the second most abundant volatile organic compound in the troposphere, with mixing ratios ranging up to several tens of parts per billion (Riemer et al, 1998;Singh et al, 2000;Schade and Goldstein, 2001;Jacob et al, 2005;Wohlfahrt et al, 2015). Since it is an important precursor of carbon monoxide, formaldehyde and tropospheric ozone, it plays an important role in the global tropospheric chemistry (Tie et al, 2003;Millet et al, 2006;Duncan et al, 2007;Choi et al, 2010;Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The most important sources of acetone are the oxidation of propane and higher hydrocarbons, and direct biogenic and biomass burning emissions [Singh et al, 1994[Singh et al, , 1995[Singh et al, , 2000. Propane and some NMHCs are not explicitly represented in the chemistry scheme; therefore we followed the approach of Wang et al [Olivier et al, 1996].…”
Section: Introductionmentioning
confidence: 99%